Vibrio vulnificus: An Environmental and Clinical Burden - Heng, Sing-Peng; Letchumanan, Vengadesh; Deng, Chuan-Yan; Ab Mutalib, Nurul-Syakima; Khan, Tahir M.; Chuah, Lay-Hong; Chan, Kok-Gan; Goh, Bey-Hing; Pusparajah, Priyia; Lee, Learn-Han (Frontiers in Microbiology, 2017)
Vibrio vulnificus is a Gram negative, rod shaped bacterium that belongs to the family Vibrionaceae. It is a deadly, opportunistic human pathogen which is responsible for the majority of seafood-associated deaths worldwide. Vibrio vulnificus infection can be fatal as it may cause severe wound infections potentially requiring amputation or lead to sepsis in susceptible individuals. Treatment is increasingly challenging as Vibrio vulnificus has begun to develop resistance against certain antibiotics due to their indiscriminate use. This article aims to provide insight into the antibiotic resistance of Vibrio vulnificus in different parts of the world as well as an overall review of its clinical manifestations, treatment and prevention. Understanding the organism’s antibiotic resistance profile is vital in order to select appropriate treatment and initiate appropriate prevention measures to treat and control Vibrio vulnificus infections, which should eventually help lower the mortality rate associated with this pathogen worldwide.